The Effect of Ca and Mg Concentrations and Quantity and Their Correlation with Caries Intensity in School-Age Children. (8th May 2018) - Sejdini, Milaim; Meqa, Kastriot; Berisha, Nora; Çitaku, Ekrem; Aliu, Nora; Krasniqi, Sokol; Salihu, Sami
Abstract : Introduction . Saliva is a watery product formed by the salivary glands and secreted in the mouth. Besides the fundamental factors, saliva with its ingredient is one of the main etiologic factors of caries presence. In the development of dental caries, the relationship between demineralization and remineralization is influenced by the presence of saliva, which facilitates the transportation of ions, oral bacteria, and fermentable carbohydrates to the exposed surfaces of teeth. The main components of saliva electrolytes are sodium, calcium, copper, magnesium, bicarbonates, and organic phosphates. Increase in calcium level in the remineralization solution may enhance the deposition velocity of minerals in the caries lesion. Magnesium, except the similar role as calcium, takes an active part in cellular reparation process. Materials and Methods . In this study were included students of age 12-13. Students were divided into three groups; the first group included caries-free children, the second group with DMF = 1–6, and the third group with DMF > 6. Fully stimulated and nonstimulated saliva was collected in sterile graded patches in the morning hours, due to the circadian rhythm in 5-minute length. Chemical analyzes have been conducted at the Faculty of Chemistry, Ss. Cyril and Methodius University in Skopje. Statistical processing has been performed at the Medical Faculty, at the Institute of Medical Statistics in Skopje. Results . Depending on the DMF, before and after stimulation, regarding Ca level, no significant differences were found. However, the Ca level prior to stimulation is significantly higher in the second group compared to the third one. Also, the amount of Ca after stimulation in the first group was significantly higher. No significant differences in Mg level and amount were found prior to and after stimulation, while the amount of Mg after stimulation had a significant difference between groups. Conclusion . Saliva mineral analysis has shown significant differences in quantitative and qualitative components between examining groups. The decrease of calcium molality in saliva might play a significant role in caries occurrence; thus, we may suppose that saliva calcium level significantly influences hard dental tissues defense mechanism. Magnesium levels after stimulation showed a significant difference between groups I and III and no significant differences between groups I and II. Magnesium level and amount correlate with calcium level, favoring elemental caries resistance.